Comparative Examinations of99mTc-DMS Preparations Obtained by Labelling Dimercaptosuccinate Kits with Different Formulations - Vanlić-Razumenić, N. (Nuklearmedizin - NuclearMedicine, 1981)
The chemical and biological characteristics of two dimercaptosuccinate kits were examined and compared: TcP-5 (produced at the Boris Kidrič Institute - Vinča) in the freeze-dried form and MPI - the aqueous solution of tin dimercaptosuccinate. The radiochemical composition of the injection solutions was examined by various methods and the method of ascending paper chromatography in 50% aqueous methanol was found as satisfactory. Both preparations had similar compositions. Both preparations showed maximum renal concentrations 3—4 hrs after injection. Liver uptake of MPI was higher than that of TcP-5. The bench-life of both preparations was compared by measuring organ distribution. TcP-5 had a bench-life at least six hrs with a kidney/liver uptake ratio from 5.60 to 8.52, whereas MPI had a satisfactory bench-life of less than half an hour after labelling; thereafter, hepatic concentration rose and the kidney/ liver uptake ratio dropped to 1.64.